Bio- and multifunctional polymer architectures : preparation, analytical methods and applications - Appelhans, Dietmar; Haag, Rainer; Voit, Brigitte; Welzel, Petra B. (Hoboken, New Jersey : John Wiley & Sons, 2016)
This reference/text addresses concepts and synthetic techniques for the preparation of polymers for state-of-the-art use in biomedicine, synthetic biology, and bionanotechnology.
Terminology -- Preparation methods and tools -- Analytical methods -- Multifunctional polymer architectures -- Functional materials and applied systems.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Polymers -- Biotechnology; Polymers in medicine; Biomedical materials; Biomedical materials; Polymers -- Biotechnology; Polymers in medicine; TECHNOLOGY & ENGINEERING / Chemical & Biochemical; Electronic books